Job Satisfaction of Veterinary Officers in Rajasthan: An Empirical Study. (June 2014) - Agrawal, Vinita; Agrawal, Vinod Kumar
The job satisfaction of an employee is a topic that has received significant attention by managers and researchers. The effective achievement of organisational goals and objectives largely depends upon satisfied employees. Job satisfaction is one of the several dimensions of the employee satisfaction. In the present day organisation scenario, it has a vital importance. As the scenario stands, not much work has been undertaken by the scholars in the past to study the job satisfaction of veterinary officers in India in general and Rajasthan in particular. Hence, the researchers became curious to study the level of job satisfaction among the veterinary officers in Rajasthan. The population of the study is finite and consists of heterogeneous veterinary officers in terms of caste, length of service, level of education, working place, etc. The study is a sample type enquiry, mainly focusing on the analysis of descriptive characteristics of job-satisfaction/dissatisfaction of veterinary officers. The sampled veterinary officers have been identified by using a stratified random sampling technique so as to ensure that the sample is representative of the population. The analytical design includes preparation of univariate tables and calculation of summary figures like averages and percentages. Non-parametric tests like Chi-Square test, Sign test and Kruskal Wallis test were applied at 5 per cent level of significance for testing the hypotheses. The results revealed that the parameters influencing job satisfaction of veterinary officers in Rajasthan did not have equal popularity. The veterinary officers did feel just satisfied irrespective of caste, length of service, areas of working, education and economic status. However, the major factors in achieving higher level of job satisfaction hover around stressful job work, adverse work conditions, inadequate promotional opportunities, etc., which should be duly taken care of by the management to ensure higher level of job satisfaction.